POSITION OFFENSES BY NOTARY IN MAKING AUTHENTIC DEED: REVIEWING THE NOTARY RESPONSIBILITY - Lsestari, Santi Rosiana; Anwary, Ichsan; Mispansyah, Mispansyah (Lambung Mangkurat Law Journal, 2017)
The research aims to analyze the notary’ responsibility as common officialwho conduct contempting of court in making deed and notary’ criminal responsibilityin running the deed and criminal liability of Notary in conducting its position. Thetype of research is normative-legal or also called as doctrinal research. The resultsof research indicate the form of notary’ responsibility can be administrative, civil orcriminal responsibility. Especially the notary’ criminal responsibility is not clearlyregulated in the Notary Act, but its responsibility is very dependent on “deliberate”(opzet) in notay’ conduct. In making the deed, the notary shall be responsible forthe deeds which are made there or which are intentional mistake, on the contrary ifthe element of mistake occurs from the parties confronting, so as long as the Notaryconducitng ith authority in accordance with the laws and regulations, the Notaryconcerned cannot be requested accountability, since the Notary simply records whatthe parties are saying to be contained into a deed.